Pengembangan Bahan Ajar Menulis Makalah dan Laporan Penelitian pada Program Studi PBSI di Universitas Baturaja - Muhamad Doni Sanjaya (Jurnal Educative: Journal of Educational Studies, 2019)
This study aims to (1) describe the need for textbook in writing learning to write papers and research reports that’s become as the development of instructional material, (2) design an appropriate textbook to students’ needs analysis, (3) develop the textbook of writing papers and research reports at the two-semester, Study Program of Language and Literature Indonesian, Faculty of Teacher Training and Education, University of Baturaja, and, (4) determine the potential effects of writing papers and research reports development of textbook on learning outcomes. This study is a research and development. Subjects in this study were students of Language and Literature Indonesian, the Faculty of Teacher Training and Education, University of Baturaja amounted to 23 students. The results of the research indicated that the textbook writing papers and research reports as the result of this development have the potential effects to influence and improve student’s understanding of the materials on the course of writing in a universityPenelitian ini bertujuan untuk (1) mendeskripsikan kebutuhan buku teks dalam pembelajaran menulis makalah dan laporan penelitian yang dijadikan bahan ajar pengembangan, (2) merancang buku teks yang sesuai dengan analisis kebutuhan mahasiswa, (3) mengembangkan buku teks menulis makalah dan laporan penelitian di semester 2 Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, (4) mengetahui pengaruh potensial pengembangan buku teks menulis makalah dan laporan penelitian terhadap hasil belajar. Penelitian ini merupakan penelitian dan pengembangan. Subjek dalam penelitian ini adalah mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja sebanyak 23 mahasiswa. Hasil penelitian menunjukkan bahwa buku teks Menulis Makalah dan Laporan Penelitian hasil pengembangan ini mempunyai pengaruh potensial dalam meningkatkan kemampuan dan pemahaman mahasiswa terhadap materi-materi menulis di perguruan tinggi.